TRANSLATION STRATEGIES ON SITES OF THE PORTUGAL TOURISM REGIONS: A CORPUS-BASED STUDY - Moreira, Adonay Custódia dos Santos (2019)
In Portugal, tourism is an economic activity that generates significant income and its marketing beyond the national market increasingly relies on the creation of multilingual websites. This paper examines a corpus of texts in Portuguese and their translations into English, all of which sourced at the websites of Portuguese Tourism Regions, so as to show how translators add information which doesn’t exist in the original text. Thus, by examining this specific feature of translated official websites promoting Portugal abroad, one intends to highlight the importance of translation strategies in marketing tourist destinations. The added information can help to build a particular image of a region. The theoretical and methodological support is provided by Corpus Linguistics.